2011
DOI: 10.2208/jscejam.67.i_503
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic steps formed by turbidity currents

Abstract: Levees of channels formed due to turbidity currents on submarine fans are often covered with step like bedforms. Circumstantial evidences emerged with numerical and experimental studies have suggested these sediment waves should probably be cyclic steps. The formation of cyclic steps in sub-aqueous environments through a mathematical perspective is presented in this research. A mathematical model preserving essential physics of the system is solved for one step wave length to obtain a preserved step shape of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Izumi and Yokokawa [10] performed a theoretical analysis to explain the formation of cyclic steps in mixed bedrock-alluvial channels. As for cyclic steps formed due to turbidity currents in submarine environments, Dias et al [11] have proposed the first analytical model, to the authors' knowledge. Their model used variables in the critical regime in the Froude sense to normalize all the main variables, such as the layer thickness of turbidity currents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Izumi and Yokokawa [10] performed a theoretical analysis to explain the formation of cyclic steps in mixed bedrock-alluvial channels. As for cyclic steps formed due to turbidity currents in submarine environments, Dias et al [11] have proposed the first analytical model, to the authors' knowledge. Their model used variables in the critical regime in the Froude sense to normalize all the main variables, such as the layer thickness of turbidity currents.…”
Section: Introductionmentioning
confidence: 99%
“…However, we establish the governing equations by integrating over the highly concentrated lower layer of turbidity currents based on the model of Luchi et al [14] rather than from the bottom to infinity. We coupled with the governing equations of long-runout turbidity currents and the Exner equation as in the model by Dias et al [11] and Izumi [13]. Taki and Parker [1] have studied the subaqueous equivalent of submarine cyclic steps and found that cyclic steps migrate upstream without changing their forms.…”
Section: Introductionmentioning
confidence: 99%